The Cynicism of Advocates as Law Enforcers: An Effort to Improve Yourself : the critical thinking important for a law degree - Alam Suryo Laksono (Dinasti Research, 2024)
The advocate profession is called a law enforcer by the Advocate Law, but at the implementation level there are limitations, when the presence of an advocate is limited to an incapacitated person who is threatened with a sentence of more than 5 years (vide KUHAP). This has become ingrained into a misguided understanding among society. Ironically, there is an assumption that advocates can be used or vice versa. In fact, it is clear that at each level there is room for lawyers to enter, from the level of investigation, fingerprinting, prosecution to fact testing at trial by the court. This writing specification is in descriptive form using juridical analysis on the basis of highlighting logical strategies as the main work methodology. This scribble is made to recognize applicable ideas, rules and principles by utilizing literature and positive law. Foundation of the Law on Advocates and KUHAP. Arriving at the conclusion, namely that it is difficult for advocates to be accepted as law enforcers because there is no intimacy either with regulations or with fellow enforcement officers, so it is difficult to make out intimately in law enforcement in abstracto with law enforcement in concreto. Cynicism towards advocates as law enforcers is limited to rights in the form of granting power of attorney. His presence is not an obligation in every case, what is very important at the initial stage is the process of making light of the incident with evidence which is often met with the need to meet the prosecutor's P21